Prognostic Factors Associated With Survival in Patients With Diffuse Astrocytoma - Liu, Shuo; Liu, Xiaoqiang; Zhuang, Weiduan (Frontiers in Surgery, 2021)
Background Diffuse astrocytoma (DA) is a rare disease with inadequately understood epidemiological characteristics and prognosis. Identification of the factors associated with the survival in DA patients is therefore necessary. In this study, we aim to investigate the clinicopathological characteristics of DA to delineate factors influencing the survival of DA. Methods A population-based cohort study was conducted, utilizing prospectively extracted data from the Surveillance, Epidemiology and End Results (SEER) database. Patients with histological diagnosis of DA in the SEER database from 1973 to 2017 were included. Results A total of 799 participants with DA were included, consisting of 95.9% fibrillary astrocytoma and 4.1% protoplasmic variants. The average age of participants was 41.9 years, with 57.2% being male. The majority of the population was white (87.5%). More than half (53.9%) of patients were married. DA arose in the cerebrum mostly (63.8%). 71.6% of the population had received surgical treatment. The overall 1-, 3-, 5- and 10-year survival rate were 73.7%, 55.2%, 49.4% and 37.6%, respectively. Kaplan-Meier analysis showed that age at diagnosis, marital status, primary tumor site, tumor size and surgery were possibly associated with cancer specific survival (CSS) (p<0.05). Multivariate Cox proportional hazard analysis indicated that surgery was a protective factor whereas older age, larger tumor size and tumor in brainstem were harmful factors for patients with DA. Moreover, a nomogram predicting 5- and 10-year survival probability for DA was developed. Conclusions Age, primary tumor site, tumor size and surgery were associated with the survival of patients with DA.